The PD1 inhibitory pathway and mature dendritic cells contribute to abacavir hypersensitivity in human leukocyte antigen transgenic PD1 knockout mice. (November 2021) - Song, Binbin; Aoki, Shigeki; Liu, Cong; Susukida, Takeshi; Kuwahara, Saki; Ito, Kousei
Highlights: Abacavir-induced severe skin hypersensitivity could be reproduced in mice. PD1 knockout facilitated Abacavir-induced CD8 T cell activation. CD4 T cell depletion could promote sufficient DC maturation. PD1 knockout and CD4 T cell depletion could lead to CD8 T cells proliferation. Abstract: Based on recent genome-wide association studies, abacavir-induced hypersensitivity is highly associated with human leukocyte antigen (HLA)-B*57:01 allele. However, the underlying mechanism of this occurrence is unclear. To investigate the underlying mechanism, we developed HLA-B*57:01 transgenic mice and found that application of abacavir could cause CD8 T cell activation with elevation in PD1 expression; however, severe skin hypersensitivity was not observed. To eliminate the immunosuppressive effect of PD1, HLA-B*57:01 transgenic/PD1 knockout (01Tg/PD1) mice were generated by mating HLA-B*57:01 transgenic mice and PD1 knockout mice. Thereafter, 01Tg/PD1 mice were treated with abacavir. Similar to the above results, severe skin hypersensitivity was not observed. Therefore, we treated 01Tg/PD1 mice with an anti-CD4 antibody to deplete CD4 T cells, followed by abacavir topically and orally. Severe abacavir-induced skin hypersensitivity was observed in 01Tg/PD1 mice after depletion of CD4 T cells, in addition to significant CD8 T cell activation and dendritic cell maturation. Taken together, we succeeded in reproducing severe skin hypersensitivity in a mouse model. And we found that through the combined depletion of PD1 and CD4 T cells, CD8 T cells could be activated and could proceed to clonal proliferation, which is promoted by mature dendritic cells, thereby eventually inducing severe skin hypersensitivity.